(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
International Journal of Pharmaceutical Sciences and Drug Research editor announce that the article "Mechanisms of Anticancer Drugs Resistance: An Overview" by M. R. Chorawala et al. has been retracted by the International Journal of Pharmaceutical Sciences and Drug Research. This article has been retracted from publication due to plagiarism. The review article was published on March 15, 2012 and retracted on October 9, 2018.